Atopic dermatitis and lymphoma risk: a systematic review and meta-analysis - Tian, Yingjie; Li, Yujin; Chen, Yang; Yuan, Guoxing; Peng, Bowen; Su, Liang; Wu, Jie (Frontiers in Oncology, 2025)
BackgroundThe relationship between atopic dermatitis (AD) and lymphoma risk remains debate. This study systematically evaluates lymphoma risk in AD patients compared to non-AD individuals.MethodsA systematic search of PubMed, Embase, and the Cochrane Library (up to August 11, 2024) identified observational studies reporting lymphoma risk estimates for AD patients. Pooled odds ratios (OR) or relative risks (RR) with 95% CIs were calculated using a random-effects model (PROSPERO ID: CRD42024577019).ResultsOf 2,366 articles were screened, 13 studies met the inclusion criteria. AD was significantly associated with elevated lymphoma risk (OR = 2.56, 95% CI: 1.75–3.74, P < 0.001; RR = 1.23, 95% CI: 1.15–1.31, P < 0.001). The risk increased with AD severity, with severe cases showing the highest effect size (RR = 2.63; 95% CI: 1.94–3.58, P < 0.001; OR = 2.60; 95% CI: 1.71–3.96, P < 0.001). Subgroup analyses revealed high risks for Hodgkin lymphoma (HL) (RR = 1.54, 95% CI: 1.35–1.75, P < 0.001) and non-Hodgkin lymphoma (RR = 1.15, 95% CI: 1.04–1.28, P = 0.006). Notably, T-cell lymphoma (TCL) showed the highest risk (OR = 4.25; 95% CI: 1.94–9.33, P < 0.001). whereas no significant association was observed for B-cell lymphoma (OR = 1.07; 95% CI: 0.95–1.20, P = 0.271).ConclusionAD is significantly association with increased lymphoma risk, particularly HL, NHL and TCL. AD severity may amplify this risk. Future research is warranted to explore underlying mechanisms and address limitations in the current evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024577019.